(The ultimate sticker book) Bug - Kellerman, Faye (Dk Publishing UK, 1994)
The Ultimate Bug Sticker Book is a vibrant and educational collection focused on the diverse world of insects. It contains over 60 reusable stickers that allow children and enthusiasts to learn about various bug species by placing the stickers on interactive scenes. The book covers fascinating facts about insects such as beetles, butterflies, ants, and bees, explaining their habitats, life cycles, and behaviors. Combining learning with fun activities, this sticker book provides a hands-on approach to discovering the intricacies of the insect world while nurturing curiosity and creativity in young minds.